Antiexplosion Performance of Engineered Cementitious Composite Explosion-Proof Wall - Guoliang Yang; Wenjia Huang; Shuai Feng (Advances in Materials Science and Engineering)
The antiexplosion performance of an explosion-proof wall made of engineered cementitious composite was studied, using small-scale explosion-proof walls made of different materials and sizes that were subjected to on-site blasting. The dynamic responses of these walls were evaluated under blast loading using overpressure test system, digital image correlation (DIC) full-field strain testing, and high-speed photography recording of the crushing process. Analysis of the results of the overpressure and strain tests revealed the effect of the wall height on the overpressure behind the wall. Increasing the height of the explosion-proof wall can improve the protection ratio of the wall by more than 2%. The variation of full-field strain of different materials at the same burst ratio was obtained. The engineered cementitious composite explosion-proof wall was obviously superior to that of ordinary concrete in strain control on the back-explosion surface. These theoretical results provide references for the design of explosion-proof walls.